2014
DOI: 10.1007/s00062-014-0301-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MR Imaging Findings of Cortical Vein Thrombosis at 3 T

Abstract: Besides the hyperintense CS, with additional evaluation of the presence of CSS, DWI can provide an additional clue in CVT patients and may suggest its diagnosis, which is important in clinically unsuspected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Among the included studies, 16 were retrospective in desig ns [ 2 , 3 , 6 , 8 , 10 , 11 , 13 , 18 , 20 - 23 , 25 , 26 , 36 , 37 ] and three were the case reports [ 7 , 15 , 33 ]. In all, 443 patients with CVT were subjected to DWI examinations in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the included studies, 16 were retrospective in desig ns [ 2 , 3 , 6 , 8 , 10 , 11 , 13 , 18 , 20 - 23 , 25 , 26 , 36 , 37 ] and three were the case reports [ 7 , 15 , 33 ]. In all, 443 patients with CVT were subjected to DWI examinations in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although, we have observed that hyperintense signal on DWI is associated with low sensitivity to detect CVT, however, the hyperintense signal on DWI had high specificity for CVT. It is suggested that DWI can provide an additional clue for the diagnosis of CVT which could be important in clinically unsuspected patients [ 37 ]. By using DWI, Favrole et al [ 11 ] detected 20 occluded veins or sinuses in 12 patients (41%) with recent CVT and suggested that the presence of hyperintense signal on DWI in occluded veins at the time of diagnosis might be predictive of a low rate of vessel recanalization 2 or 3 months later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since susceptibility effects are well known to disappear with the formation of extracellular methemoglobin, it seems to be the main reason for the non-visualization of COVT in these 2 cases [ 3 , 4 , 8 ]. Fortunately, the clots were easily identifiable on T1 TSE, DWI and FLAIR sequences in both cases [ 17 ]. Our results highlight that SWI is a vital sequence to evaluate COVT as it can identify the majority of COVT on its own.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, it has variable clot signal depending on the age of the clot, field strength, haemoglobin level, image sequence and other factors. There should be absent flow signal on the MR venogram and possible diffusion weighted imaging (DWI) changes due to associated infarction 18. Mortality has been reducing over the last few years, probably due to early recognition and treatment with anticoagulants 19…”
Section: Venous Infarctionmentioning
confidence: 99%